Efektivitas Kegiatan P5 dalam Meningkatkan Kreativitas Peserta Didik Kelas VIII SMPN 281 Jakarta - Azlea Mayasya Aziz; Desy Safitri; Sujarwo (JIMAD: Jurnal Ilmiah Mutiara Pendidikan, 2024)
Creativity is an essential aspect in education to prepare learners to face complex future challenges. P5 activities (P5 Student Profile Strengthening Project) serve as an effort to enhance the creativity of students at SMPN 281 Jakarta. This research employs a quantitative descriptive approach to evaluate the effectiveness of P5 activities in improving the creativity of eighth-grade students. Data were collected through questionnaires completed by 70 students and interviews with 3 teachers, including the P5 coordinator. The research findings indicate that the effectiveness of P5 activities in enhancing student creativity reaches a very high category, with a percentage of 92%. Student creativity experiences a significant improvement, particularly in generating new ideas, viewing problems from various perspectives, seeking alternative solutions, and daring to undertake challenging tasks. However, there is still room for improvement, especially in aspects of creativity related to unconventional thinking to express oneself. Teachers and the P5 coordinator play crucial roles in designing and implementing P5 activities to create an environment conducive to student creativity growth. In conclusion, P5 activities are effective in enhancing the creativity of eighth-grade students at SMPN 281 Jakarta, yet continuous improvement is needed to achieve maximum creative potential.